Circulating tumor cells: utopia or reality?. (September 2013) - Conteduca, Vincenza; Zamarchi, Rita; Rossi, Elisabetta; Condelli, Valentina; Troiani, Laura; Aieta, Michele
Circulating tumor cells (CTCs) could be considered a sign of tumor aggressiveness, but highly sensitive and specific methods of CTC detection are necessary owing to the rarity and heterogeneity of CTCs in peripheral blood. This review summarizes recent studies on tumor biology, with particular attention to the metastatic cascade, and the molecular characterization and clinical significance of CTCs. Recent technological approaches to enrich and detect these cells and challenges of CTCs for individualized cancer treatment are also discussed. This review also provides an insight into the positive and negative features of the future potential applications of CTC detection, which sometimes remains still a 'utopia', but its actual utility remains among the fastest growing research fields in oncology.